(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article examines the importance of early detection and treatment of chronic bronchitis, as well as the structure of the bronchi. Chronic bronchitis is a long-term inflammation of the bronchial tubes, characterized by persistent cough and phlegm production. If chronic bronchitis is not diagnosed early, the patient’s condition will gradually worsen. For example, breathing difficulties may increase. In this case, oxygen deficiency and sometimes lung failure may occur. Also, if necessary medical treatment is not carried out , chronic bronchitis can progress to chronic obstructive pulmonary disease (COPD), pulmonary hypertension and cardiovascular disease. In the early stages of the disease, symptoms may not be noticeable, so early detection is very important to slow down the progressive damage to the lungs and improve the patient’s quality of life.